Sand Floor for Farmed Blue Foxes: Effects on Claws, Adrenal Cortex Function, Growth and Fur Properties - Ahola, Leena; Koistinen, Tarja; Mononen, Jaakko (International Journal of Zoology, 2009)
Farmed blue foxes (Vulpes lagopus) are traditionally housed on mesh floors where they are unable to perform certain species-specific behaviours, such as digging, which may compromise the animals' welfare. This study describes how a possibility to use in-cage sand floor affects welfare-related variables like growth of the claws, adrenal cortex function, and fur properties in juvenile blue foxes. The foxes (N=32) were housed in male-female sibling pairs in an outdoor fur animal shed in cage systems consisting of two traditional fox cages. For the eight male-female sibling pairs of the Control group, there was a mesh floor in both cages of each cage system, whereas for the eight pairs of the Sand group there was a mesh floor in one cage and a 30–40 cm deep earth floor in the other cage. The results show that sand floor is beneficial for the wearing of the claws of foxes. Furthermore, an early experience of sand floor may have positive effects on the foxes' fur development. The results, however, also suggest that there might appear welfare problems observed as disturbed claw growth and increased adrenal cortex activation if foxes that are once provided with clean and unfrozen sand floor are not allowed to enjoy this floor all the time.